1996
DOI: 10.1177/009318539602400206
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, Timing and Circumstances of Disclosure in Therapy of Recovered and Continuous Memories of Abuse

Abstract: Seventeen patients who had recovered memories of abuse in therapy participated in a search for evidence confirming or refuting these memories. Memories of abuse were found to be equally accurate whether recovered or continuously remembered. Predictors of number of memory units for which evidence was uncovered included several measures of memory and perceptual accuracy. Recovered memories that were later supported arose in psychotherapy more typically during periods of positive rather than negative feeling towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 0 publications
1
58
0
3
Order By: Relevance
“…Citing two studies (Dalenberg, 1996;Williams, 1995), Dalenberg et al (2012) claimed that recovered and continuous memories are This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Citing two studies (Dalenberg, 1996;Williams, 1995), Dalenberg et al (2012) claimed that recovered and continuous memories are This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Commentmentioning
confidence: 99%
“…Dalenberg (1996) reported that 17 patients undergoing psychotherapy for problems associated with sexual abuse they had never forgotten remembered additional abuse episodes that perpetrators corroborated as often as they did the always-remembered episodes. Although Dalenberg (1996) interpreted these recollections as evidence of patients recovering from dissociative amnesia, ordinary memory mechanisms easily explain these findings. Indeed, it is little wonder that discussing certain abuse episodes would cue additional recollections in people with extensive histories of CSA.…”
Section: Commentmentioning
confidence: 99%
“…Researchers who have specifically sought to evaluate the accuracy of self-reports of potentially disturbing events have generally found that such reports are not alarmingly inaccurate (e.g., Watt & Stewart, 2003) nor are inaccuracies obviously correlated with such variables as psychopathology (Brewin, Andrews, & Gotlib, 1993) or with the availability of the memories over time (Dalenberg, 1996;Williams, 1995). Indeed, as Williams (1995) A particular problem for interpreting results using our instrument arises if errors, particularly false negatives, are more likely when there are abusive events involving a close other.…”
Section: Some Limitations Of Our Researchmentioning
confidence: 99%
“…Zowel herinneringen hervonden buiten een therapiesituatie, als tijdens psychotherapie hervonden herinneringen zijn overigens niet a priori minder betrouwbaar dan herinneringen aan traumatische ervaringen die altijd beschikbaar waren (Scheflin et al, 1996 ;Dalenberg, 1996 ;Herman et al, 1997 ;Brown et al, 1998).…”
Section: Codeerspecificiteitunclassified
“…Zo zijn er aanwijzingen voor dat de accuratesse van de herinneringen aan trauma kan toenemen in de loop van de behandeling (Dalenberg, 1996). In verschillende onderzoeken bleek dat in de helft (Kluft, 1997) of meer (Coons, 1994;Dalenberg, 1996 ;Martinez-Taboas, 1996;Lewis et al, 1997) van de gevallen onafhankelijke evidentie kon worden verkregen voor de accuratesse van in elk geval de essentie van zowel continue als na een periode van amnesie terugkerende herinneringen van traumatische gebeurtenissen. Kan dergelijke evidentie niet worden achterhaald dan zullen patie¨nt en therapeut moeten leven met waarschijnlijkheden in plaats van zekerheden.…”
Section: Impliciete Herinneringenunclassified